2015
DOI: 10.1007/s00441-015-2242-4
|View full text |Cite
|
Sign up to set email alerts
|

Brain-midgut cross-talk and autocrine metabolastat via the sNPF/CCAP negative feed-back loop in the American cockroach, Periplaneta americana

Abstract: Immunohistochemical reactivities against short neuropeptide F (sNPF-ir) and crustacean cardioactive peptide (CCAP-ir) were detected in both the brain-subesophageal ganglion (Br-SOG) and midgut epithelial cells of the male American cockroach, Periplaneta americana. Four weeks of starvation increased the number of sNPF-ir cells and decreased the CCAP-ir cells in the Br-SOG, whereas refeeding reversed these effects. The contents of sNPF in the Br-SOG, midgut and hemolymph titer decreased in response to an injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 29 publications
(57 reference statements)
0
27
0
Order By: Relevance
“…Especially, the effect of CCAP deserves attention, since it has been shown in locusts that this neuropeptide stimulates in vitro release of AKH from corpora cardiaca (Veelaert et al, 1997). Further, it has also been proved that CCAP elevates the amylase activity in the midgut of P. americana (Sakai et al, 2004) and that it occurs even in epithelial cells (apart from the brain-suboesophageal ganglion) of the same organ (Mikani et al, 2015). Later on the same group (Sakai et al, 2006) proved that incubation of cockroach midgut in the CCAP presence significantly increased amylase activity within 2-3 h after the hormonal application.…”
Section: Hormonal Control Of Amylase Activitymentioning
confidence: 99%
“…Especially, the effect of CCAP deserves attention, since it has been shown in locusts that this neuropeptide stimulates in vitro release of AKH from corpora cardiaca (Veelaert et al, 1997). Further, it has also been proved that CCAP elevates the amylase activity in the midgut of P. americana (Sakai et al, 2004) and that it occurs even in epithelial cells (apart from the brain-suboesophageal ganglion) of the same organ (Mikani et al, 2015). Later on the same group (Sakai et al, 2006) proved that incubation of cockroach midgut in the CCAP presence significantly increased amylase activity within 2-3 h after the hormonal application.…”
Section: Hormonal Control Of Amylase Activitymentioning
confidence: 99%
“…Mikani [22] showed that sNPF as both a neuropeptide and a midgut factor that suppresses α-amylase, protease and lipase activities during starvation this demonstrates an intricate interplay between the brain and midgut to regulate digestive activities. This finding indicated that enzyme activities were downregulated by sNPF [21,22].…”
Section: Discussionmentioning
confidence: 79%
“…Veenstra and Lambrou [38] isolated a large amount of sNPF from the midgut of P. americana. Changes in peptide content in paraneuronal cells are correlated with the state of digestion of insects [21,50]. The number of sNPF-ir paraneuronal cells increased during 4 weeks of starvation and decreased after 3 h of refeeding [22].This suggests that the nutritional input was sensed by the midgut and CCAP is released to the hemocoel that stimulate the secretion of CCAP from the brain, constituting a large feed-forward loop.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Competitive ELISA was performed as previously described. 19) Briefly, after dissection of the midgut in TBS, homogenization, and centrifugation (4000×g, 4°C, 15 min), the supernatant was used as an assay sample. After coupling synthetic AST-6 and to BSA with dimethyl suberimidate (Sigma-Aldrich, USA) and preparing an AST-A-BSA conjugate, the plates were coated with AST-6-BSA (0.6 µg/mL per well) in 0.05 M sodium carbonatebicarbonate buffer (pH 9.0).…”
Section: Competitive Elisamentioning
confidence: 99%